Generation Z's Human Resource Management Strategies in the Digital Era - Astuti Setianingsih, Puji; Hadi Isnanto, Samto (Dinasti International Journal of Digital Business Management, 2025)
This research aims to explore human resource Management (HRM) strategies employed by Generation Z (Gen Z) in the digital era. The focus of the study is on the integration of digital technology, ethical awareness, and personal values in HR decision-making. Gen Z tends to utilize digital platforms for recruitment, communication, and performance management, leveraging technology to enhance workplace efficiency and employee management. The research adopts a descriptive qualitative approach to identify the challenges and risks Gen Z faces in HRM, such as concerns over data security, online communication, and maintaining ethical standards in the workplace. Personal values and ethical considerations also influence HR decisions within Gen Z's approach. This study aims to provide insights that can help develop more effective HR strategies and policies tailored to the needs and preferences of Gen Z in the digital era.